The Effect of Sales Growth, Capital Expenditure, and Working Capital Efficiency on Indonesian-Listed-Consumer-Goods Firms’ Financial Performance with Capital Structure as Moderating Variable - Youlanda Githa Dovita; Andewi Rokhmawati; Ahmad Fauzan Fathoni (Indonesian Journal of Economics, Social, and Humanities, 2019)
This study aims to determine the effect of sales growth, capital expenditure and working capital efficiency on financial performance which is moderated by the capital structure. The population in this study was all consumer goods industry firms listed on the Indonesia Stock Exchange in 2014-2017. Sampling in this study was based on purposive sampling and obtained as many as 35 firms. The analytical method used was Partial Least Square (PLS) analysis. The results showed that sales growth and capital expenditure do not significantly affect capital structure; working capital and capital structure has a positive and significant effect on financial performance. Meanwhile, as a moderating variable, capital structure is not able to moderate the influence of sales growth on financial performance. Capital structure weakens the effect of capital expenditure and efficiency working capital on financial performance.